Landmines - Jean-Louis Arcand; Aude-Sophie Rodella-Boitreaud; Matthias Rieger (Graduate Institute of International and Development Studies, 2011)
This paper estimates the causal impact of landmines on child health and household expenditures in Angola by exploiting geographical variations in landmine intensity. We generate exogenous variation in landmine intensity using the distance between communes and rebel headquarters. As predicted by our theoretical model of rebel mining, landmine intensity is found to be a decreasing function of the distance to a set of rebel headquarters. Instrumental variables estimates, based on two household surveys and the Landmines Impact Survey, indicate that landmines have large and negative effects on weight-for-age, height-for-age and household expenditures. We discuss our results with respect to the costs and benefits of landmine clearance.
Keywords: 330; civil war; landmines; instrumental variables; household expenditures; height-for-age; weight-for-age; Angola; Rüstungsgut; Kriegsschaden; Kinder; Gesundheit; Verbraucherausgaben; Instrumentalvariablen-Schätzmethode; Angola